Establishment of the first marine mollusk cell line from scallop (Chlamys farreri) trochophore - Zhenkui Qin; Aichang Ji; Meng Yan; Danwen Liu; Xixi Li; Xiaoli Hu; Zhifeng Zhang (Aquaculture Reports)
Cell lines are indispensable tools in biological studies. Decades of attempts have failed to establish a cell line in marine mollusks, which contribute to 70 % of the mariculture production in China. In the present study, FBS, scallop serum, scallop ovarian extracts, and FeCl3 were added to the L-15 basic medium to develop an optimized culture medium (L15-CFIIIFe) for culturing trochophore larval cells of Chlamys farreri, an important mariculture scallop in China. C. farreri trochophore larval (CfT) cells exhibited proliferative activity, and a CfT cell line was successfully established, which was passaged for 155 generations in vitro. The origin of the CfT cell line was verified as C. farreri using internal transcribed spacer (ITS) and 18 s rRNA gene amplification, genomic in situ hybridization (GISH), and karyotype analysis. The CfT cell line was a mixture of cells of three sizes (5–7, 9–12, and 18–22 μm), with a population doubling time of 75.6 h. Immunofluorescence detection of KLF4, c-MYC, MYOSIN, and 5-HT indicated that CfT cells may possess a certain degree of pluripotency. Four gene transfer methods were tested in the CfT cell line; however, the transfer efficiency (0.5 %-1 %) requires further optimization. We successfully established the first marine mollusk cell line, providing a valuable cellular tool for mollusk studies.